Pengaruh Modeling Langsung Terhadap Perencanaan Karir Siswa di MAN 2 Model Makassar - Fahmi, Ainul (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
The study aims at discovering the description of students’ career plan at MAN 2 Model Makassar before and after the treatment and examining whether direct modeling has influence on students’ career plan at Man 2 Model Makassar.The type of this study was quantitative research with experiment research. Samples were chosen by employing random sampling technique with drawing method. Data collected were conducted by using two instruments, namely career plan scale and observation. Data analysis employed descriptive data analysis and inferential data analysis. The results of the study reveal that (1) the level of career plan of grade XI students at MAN 2 Model Makassar before being given the treatment in this case the direct modeling was in medium category. However,after being given the treatment,the level of career plan improved or was in high category,(2) the implementation of direct modeling gave influence in improving students’ career plan, meaning that when the direct modeling was applied, it would help improving the students’ career plan at MAN 2 Model Makassar.